2022
DOI: 10.3390/vaccines10040500
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Willingness and Vaccine Uptake among Healthcare Workers: A Single-Center Experience

Abstract: Healthcare workers (HCWs) are at higher risk of developing COVID-19 due to their professional exposition to the SARS-CoV-2 virus. This study assesses the intention of vaccination against COVID-19 before the vaccines were approved, and the rate of vaccine uptake during the first nine months of immunization among HCWs. A cross-sectional seroprevalence study was carried out during July 2020 in University Clinical Hospital Center Bezanijska Kosa in Belgrade, Serbia that included 62.8% of all HCWs. Besides serologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“…We assessed the full texts of 36 articles, and we excluded 11 applying our inclusion and exclusion criteria. Finally, we included 25 studies in our systematic review and meta-analysis [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. The flow diagram according to PRISMA guidelines is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We assessed the full texts of 36 articles, and we excluded 11 applying our inclusion and exclusion criteria. Finally, we included 25 studies in our systematic review and meta-analysis [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. The flow diagram according to PRISMA guidelines is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Main characteristics of the studies included in our review are presented in Table S1 . We found 25 studies including 491,624 vaccinated HCWs, while the full sample included 555,561 HCWs, ranging from 172 to 356,053 [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. The mean percentage of females was 67.3% (standard deviation = 19.9), and the mean age of the full sample was 39.2 years (standard deviation = 6.2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…COVID-19 vaccination acceptance has also varied by occupation. Multiple studies have identified greater vaccine hesitancy in nurses, and higher rates of vaccine acceptance are seen in physicians [20][21][22]. These limited and contradictory findings further strengthen the need for additional studies to define how sociodemographic characteristics affect COVID-19 vaccine hesitancy among HCWs.…”
Section: Introductionmentioning
confidence: 99%